Pemberdayaan Desa Siaga Untuk Mengurangi Ibu Hamil Kek (Kurang Energi Kronis) Dalam Upaya Pencegahan Stunting - Syahrianti, Syahrianti; Halijah, Halijah; Heyrani, Heyrani; Farming , Farming (Jurnal Stunting Pesisir dan Aplikasinya, 2023)
Malnutrition for a long time in pregnant women will cause pregnant women to experience a condition called Chronic Energy Deficiency (CED). Almost all developing countries have experienced SEZ problems, one of which is Indonesia. Another factor that influences the effectiveness of empowering pregnant women in efforts to handle CED is the use of health facilities. The use of health service facilities by pregnant women can be seen from the coverage of pregnancy checks, one of which is the use of antenatal care which is less than the minimum standard. Health workers play a role in empowering the community in the health sector. Health workers strive to develop learning for the community to build independence in solving health problems. The impact that will be obtained if the empowerment of alert villages for pregnant women in an effort to handle CED is not effective is related to the occurrence of cases of stunting in newborn babies, bleeding, defects in the fetus and death can also occur in the mother and baby. The community service method used is educational and participatory outreach, targeting all pregnant women, their families, especially husbands and cadres. It is hoped that this community service activity can increase the understanding of women of childbearing age about the importance of empowering Alert Villages to reduce chronic energy deficiency in pregnant women in preventing stunting.